Fiscal Policy for Health Policy Makers - Gillingham, Robert (World Bank, Washington, DC, 2014)
This paper summarizes the basic principles that should form the basis of fiscal policy. These principles encompass decisions on the functions of government, its spending, and the financing of its spending that affect economic growth, employment, inflation, and economic welfare. Although the principles are broadly applicable, it is especially important that health policy makers understand them. Ensuring access to health care is one of society's, and therefore the government's, most important goals. In meeting this goal, policy makers must be cognizant of fiscal realities; what they can reasonably expect government to achieve in the health sector and at what cost. Resources are limited, and many valuable programs in both the private and public sectors vie for them. Allocating these resources efficiently is of paramount importance, with implications for what the government does and how it finances its activities. The absolute level and share of government resources allocated to the health sector will depend on a variety of factors, but the bottom line is that health programs must compete with other government programs for scarce resources to ensure that these resources are put to their best use.